Analisis Pengaruh Penambahan Serbuk Sabut Kelapa (Cocopeat) Pada Campuran Agregat Terhadap Kuat Tekan Paving Block - Syahwanti, Hezliana; Irvhaneil, Irvhaneil (Borneo Engineering : Jurnal Teknik Sipil, 2024)
Â The use of sand in the world of construction increases every year so alternative sand companions are needed to reduce its use. One of the construction activities is making paving blocks. Paving blocks are often used for residential complex roads, sidewalks or paving yards, as a result, paving block production increases every year. This is in line with the increasing use of sand. Sand is fine grains that are physically similar to cocopeat (coconut fiber powder). Because the physical properties of cocopeat and sand are the same (Syahwanti et. al, 2021), cocopeat can be researched for use in the construction sector, especially in making paving blocks. The aim of this research is to make paving blocks with an aggregate mixture of cocopeat, sand, cement, gravel and water with a composition ratio of cocopeat and sand, namely 0%, 10%, 25% and 50%. The research method used is experimental where each sample will go through a pressure test to determine the quality of the paving blocks made. The results for the 0% cocopeat composition obtained a pressure test value of 332.25 kN. The compression test values for paving blocks with a cocopeat composition of 10% and 25% produced load values of 16.9 kN and 12.6 kN. For paving blocks with 50% cocopeat composition, the compression test value was obtained for a load of 10.65 kN. These results show that cocopeat can be used as a mixture of fine aggregates in making paving blocks and can be applied as non-structural hardening where the applied load strength is low.